Endoplasmic reticulum stress and NF‐kB activation in SARS‐CoV‐2 infected cells and their response to antiviral therapy. Issue 1 (13th August 2021) - Bartolini, Desirée; Stabile, Anna Maria; Vacca, Carmine; Pistilli, Alessandra; Rende, Mario; Gioiello, Antimo; Cruciani, Gabriele; Galli, Francesco
Abstract: Unfolded protein response (UPR) and endoplasmic reticulum (ER) stress are aspects of SARS‐CoV‐2‐host cell interaction with proposed role in the cytopathic and inflammatory pathogenesis of this viral infection. The role of the NF‐kB pathway in these cellular processes remains poorly characterized. When investigated in VERO‐E6 cells, SARS‐CoV‐2 infection was found to markedly stimulate NF‐kB protein expression and activity. NF‐kB activation occurs early in the infection process (6 hpi) and it is associated with increased MAPK signaling and expression of the UPR inducer IRE‐1α. These signal transduction processes characterize the cellular stress response to the virus promoting a pro‐inflammatory environment and caspase activation in the host cell. Inhibition of viral replication by the viral protease inhibitor Nelfinavir reverts all these molecular changes also stimulating c ‐Jun expression, a key component of the JNK/AP‐1 pathway with important role in the IRE‐1α‐mediated transcriptional regulation of stress response genes with anti‐inflammatory and cytoprotection function. The present study demonstrates that UPR signaling and its interaction with cellular MAPKs and the NF‐kB activity are important aspects of SARS‐CoV‐2‐host cell interaction that deserve further investigation to identify more efficient therapies for this viral infection.